Preening for protection: a systematic review of the antimicrobial properties of uropygial secretions - Carlos Mora‐Rubio; Luz García‐Longoria; Alfonso Marzal (Journal of Avian Biology)
Uropygial secretion might play a crucial role in avian defense by exhibiting antimicrobial properties that protect birds from various pathogens. Although there has been considerable research, the differences in methods and results have led to varying conclusions about how well it works as an antimicrobial. Despite extensive research, the differences in experimental methods and results have led to varying conclusions regarding its antimicrobial effectiveness. This review consolidates existing literature on the antimicrobial activity of uropygial secretion or related compounds against bacteria and fungi across different bird species. A comprehensive search identified 35 studies, showcasing a variety of techniques used to assess antimicrobial activity, including agar diffusion, colony‐forming unit (CFU) counting, and flow cytometry. The findings reveal a diverse range of antimicrobial effects influenced by bird species, target microorganisms, and the methodologies employed. Notably, uropygial secretion appears to be more effective against gram‐positive bacteria than gram‐negative bacteria and fungi, although these latter groups have been less extensively studied. The review also underscores significant limitations in taxonomic representation, as research has primarily focused on a limited number of bird species while many others remain underrepresented. Additionally, gaps in standardization and the predominance of in vitro studies hinder our ability to draw comprehensive conclusions about the antimicrobial potential of the uropygial secretions under natural conditions. Future research should prioritize standardizing methodologies, broadening the taxonomic scope, and investigating the combined effects of individual compounds within the secretion, including symbiotic microorganisms. Addressing these gaps will enhance our understanding of the evolutionary and ecological significance of uropygial secretion and clarify its role in avian health and defense mechanisms.